A combined experimental and computational study on the sulfoxidation by high-valent iron bispidine complexes - Jaccob, Madhavan; Comba, Peter; Maurer, Martin; Vadivelu, Prabha; Venuvanalingam, Ponnambalam (Dalton transactions, 2011)
Iron-bispidine complexes are efficient catalysts for the oxidation of thioanisole to phenylmethylsulfoxide with iodosylbenzene as oxidant. With the tetradentate bispidine ligand L1 (L1 = 2,4-pyridyl-3,7-diazabicyclo[3.3.1]nonane)) the catalytic efficiency is smaller than with the pentadentate bispidine ligand L2 (L2 = 2,4-pyridyl-7-(pyridine-2-ylmethyl)-3,7-diazabicyclo[3.3.1]nonane)). Based on the redox potentials (iron complexes with L1 are stronger oxidants than with L2) and known efficiencies in catalytic olefin oxidation and C-H activation reactions, the expectations were different. A DFT-based analysis is used to explain the apparent contradiction, and this is based on differences in the electronic ground states of the ferryl complexes as well as in the oxygen transfer transition states.
Gesehen am 04.07.2022